(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article explores the essence of the concept of intellectual potential, its role in the modern educational system, and its significance in shaping the younger generation. The author analyzes methods for developing students’ intellectual capabilities within the educational process and addresses existing challenges in this field. Furthermore, the impact of intellectual capital on the socio-economic development of society is substantiated.